Le milizie urbane: innovazioni e persistenze in età tetrarchica e costantiniana - Redaelli, Davide (Cultura giuridica e diritto vivente, 2020)
[The urban troops: innovations and continuities during the Tetrarchy and the Constantine’s era]. This paper aims to discuss the more relevant problems concerning the history of the most important military corps stationed in Rome, the vigiles, the urbaniciani, the equites singulares Augusti and the praetorians, in a period of time included between Diocletian rise and Constantine death. The closer examination of the sources shows that the rise of Diocletian was not the beginning of the decline of the Rome’s units, as claimed by some modern scholars.